Infected Dentigerous Cyst in a 14-year-old Child Associated with Unerupted Third Molar: A Case Report - Vaidya, Subhani; Limbu, Senchhema; Dikshit, Parajeeta; Malla, Manisha; Verma, Lokesh (Journal of Nepalese Association of Pediatric Dentistry, 2021)
The dentigerous cyst is a developmental odontogenic cyst, accounting for 10% of all cysts of the jaws, being the vast majority of current odontogenic cyst. Its characteristic features are unilocular radiolucent lesion which encloses permanent tooth buds or, under certain circumstances, displaced tooth buds. This paper presents a case of an infected dentigerous cyst associated with right mandibular unerupted third molar in a pediatric patient with various clinical and radiographic characteristics. The treatment comprised of proper evaluation of the past medical history, clinical, radiographic, histological examinations that helped to administer appropriate diagnosis and treatment plan; followed by complete removal of the cyst along with the involved tooth structure under general anesthesia.